2018
DOI: 10.1002/cctc.201800860
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Nanoporous Hematite Photoanodes Prepared by Electron Beam Evaporation and Au Modification

Abstract: The water oxidation efficiency of hematite photoanodes is mainly limited by low visible light absorption and short hole diffusion length. Herein, we report on production of nanoporous columnar hematite films modified with Au nanoparticles (NPs) to overcome these drawbacks. The hematite films are prepared by electron beam evaporation. By optimization of deposition conditions including film thickness, annealing and performing the evaporation under oblique angle, an efficient photoelectrochemical (PEC) performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…The contribution of light in the formation of an oxidized product can also be seen in Figure S5. The appearance of this hydrated/oxidized gold phase in the interface, the electrode/electrolyte may affect the conductivity impairing the photocatalytic performance because of the passivation layer on the surface formation, decreasing the number of the transferred charge . Most notably, it has been reported that the appearance of the oxidized gold species on metals can induce a reduction of the metal work function. ,, This implies that under PEC conditions, the presence of chemisorbed species (Au–O) plays a role in the photoactivity of AuNP.…”
Section: Resultsmentioning
confidence: 99%
“…The contribution of light in the formation of an oxidized product can also be seen in Figure S5. The appearance of this hydrated/oxidized gold phase in the interface, the electrode/electrolyte may affect the conductivity impairing the photocatalytic performance because of the passivation layer on the surface formation, decreasing the number of the transferred charge . Most notably, it has been reported that the appearance of the oxidized gold species on metals can induce a reduction of the metal work function. ,, This implies that under PEC conditions, the presence of chemisorbed species (Au–O) plays a role in the photoactivity of AuNP.…”
Section: Resultsmentioning
confidence: 99%
“…Despite with a bilayered thin film as our model system, it is easy to extend our strategy to fabricate nano‐multilayered coatings. In addition, the EBE deposition we used in this study is a powerful thermal evaporation approach to deposit nanostructured coatings with controlled thickness and superimposed nanotopographical features and enables the evaporation of metals with very high melting points and a high material utilization efficiency on the outer surface of substrates, even with complex geometries, [ 53 ] indicating a wide applicability of this approach to diverse functional metallic ions delivery.…”
Section: Resultsmentioning
confidence: 99%
“…Various strategies have been employed to overcome the limitations of hematite, including heterojunction construction, 20 doping with metals and nonmetals, [21][22][23] morphology advancement, 24 and co-catalyst loading. 25,26 Among these, forming nanoscale heterojunctions by coupling a-Fe 2 O 3 with a second semiconductor has proven effective, leveraging appropriate bandgap overlap and enhanced charge separation at the junction interfaces.…”
Section: Introductionmentioning
confidence: 99%